CREATION OF SHAREHOLDERS WEALTH: INDIAN EVIDENCE WITH EVA AND MVA - Shah, Vividh (2010)
The study examines the financial performance of few most valuable companies of India on the objective of creating wealth for its shareholders. Two popular measures namely, Economic Value Added (EVA) and Market Value Added are calculated for a sample of 22 companies for the study period of FY 2004-05 to 2008-09. Based on EVA, it identifies that approximately 82% of the sampled companies created shareholders for first three years whereas for the last two years the number drops to 63% to 72% of the companies . The study also ranks sampled companies on the basis of calculated MVA. So, the study provides data for users like investors, portfolio managers and corporate managers which can be helpful to them in some form. The research also looks at the relationship between the two variables EVA and MVA and provides statistical evidence, using regression analysis, that EVA is a positive and significant determinant of market value of a company.